Investigation of the effect of a new splash grid on natural drought wet cooling tower (NDWCT) performance - Michaels, Alain Juan-Pierre (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng)--Stellenbosch University, 2015.